Prevalence Of Dietary Deficiency In Stroke Survivors - Gaikwad, Anushka; Kanase, Suraj B. (Journal of Neonatal Surgery, 2025)
Introduction: Dietary deficit occurs when the body does not receive adequate nutrients from diet. This can contain vitamins, minerals, proteins, and other nutrients required for optimum health. Deficiencies might be caused by a poor diet, digestive issues, or medical conditions. Over time, they can cause weakness, fatigue, weak bones, low immunity, and delayed recovery. Eating a balanced diet with a range of nutrients helps prevent nutritional deficits. Dietary deficits can have significant impacts on stroke survivors, slowing down recovery and raising the risk of further health complications. Following a stroke, the body need necessary foods such as vitamins, minerals, proteins, and healthy fats to repair damaged brain cells, restore muscular strength, and enhance overall performance. Objectives: To identify whether there are any dietary deficiency in stroke survivors and the extent in which it may occur. Methods: The cross-sectional survey that was conducted in Karad City. The purpose of this survey is to determine how common dietary deficiency is in stroke survivors. Prior to conducting the survey, the ethical committee's approval was obtained. Patients were chosen based on inclusion and exclusion standards. With their permission, 100 stroke survivors participated in this study, and result was obtained by the statistician. Result: The trial, which included 100 stroke survivors aged 35-65 years, was undertaken with ethical approval. This study revealed that the prevalence of dietary deficiencies among stroke survivors is 56.40%. The deficiencies identified in stroke survivors include vitamin D, folate, calcium, potassium, and magnesium. Additionally, our findings indicate that dietary deficiencies are more prevalent among females than males, and are more common in rural populations compared to urban areas. Conclusion: Nutritional deficiencies among individuals who have survived a stroke is notably high, which has considerable consequences for their recovery and overall health in the long term. Therefore, regular assessments by healthcare professionals, along with tailored dietary interventions, are essential elements of a comprehensive care plan for stroke survivors.